A wavelet-based technique for discrimination between faults and magnetizing inrush currents in transformers. - Youssef, O.A.S.
This paper presents the development of a wavelet-based scheme, for distinguishing between transformer inrush currents and power system fault currents, which proved to provide a reliable, fast, and computationally efficient tool. The operating time of the scheme is less than half the power frequency cycle (based on a 5-kHz sampling rate). In this work, a wavelet transform concept is presented. Feature extraction and method of discrimination between transformer inrush and fault currents is derived. A 132/11-kV transformer connected to a 132-kV power system were simulated using the EMTP. The generated data were used by the MATLAB to test the performance of the technique as to its speed of response, computational burden and reliability. The proposed scheme proved to be reliable, accurate, and fast.
Keywords: 11 kV; 132 kV; 5 kHz; EMTP; MATLAB; Computational burden; Digital signal processors; Faults; Feature extraction; Magnetizing inrush currents; Power frequency cycle; Power system; Power system fault currents; Protective relaying; Reliability; Transformers; Transforms-transient analysis; Wavelet transforms; Wavelet-based technique